Kerjasama Guru dan Orang Tua Dalam Menangani Anak yang Masih Ditunggu Pada Jam Belajar di PAUD Harapan Kita di Desa Saing Rambi - Evi Rahmawati; Susilawati; Zuri Astari (Tarbiya Islamica, 2024)
This research has three research objectives, including the following: First, to find out the characteristics of children who are still waiting for learning hours at PAUD Harapan Kita in Saing Rambi Village for the 2021-2022 Student Year. Second, to find out how teachers and parents collaborate in dealing with children who are still waiting for hours at PAUD Harapan Kita in Saing Rambi Village for the 2021-2022 Student Year. Third, to find out what the implications or results of collaboration between teachers and parents are in dealing with children who are still waiting for hours at PAUD Harapan Kita in Saing Rambi Village for the 2021-2022 Student Year. The research uses a qualitative approach while this type of research is phenomenological research. There are three types of data collection techniques in this research, namely: Interview, Observation and Documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data display, drawing conclusions and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. Research result. First, cooperation between teachers and parents in handling children who are still waiting for learning hours at PAUD Harapan Kita Saing Rambi Village for the 2021-2022 academic year. Collaboration between teachers and parents is important in the child's growth and development process, so good cooperation is very helpful for children, especially children who are still experiencing problems or obstacles to learning at school. Second, a form of cooperation between teachers and parents in dealing with children who are still waiting for learning hours at PAUD Harapan Kita Saing Rambi Village for the 2021-2022 academic year. Consists of several, namely: 1) Parenting, 2) Communication, 3) Volunteering, 4) Parental involvement in children's learning at home, 5) Decision making, 6) Collaboration with community groups. Third, the implications or results of collaboration between teachers and parents in dealing with children who are still awaited during learning hours at PAUD Harapan Kita Saing Rambi Village for the 2021-2022 academic year. Providing guidance and motivation for children's learning, providing stimulus to children wholeheartedly with love and helping children learn, play and interact with their classmates